Transnasal Endoscopic Evaluation of Swallowing: A Bedside Technique to Evaluate Ability to Swallow Pureed Diets in Elderly Patients with Dysphagia - Torao Sakamoto; Akira Horiuchi; Yoshiko Nakayama (Canadian Journal of Gastroenterology)
BACKGROUND: Endoscopic evaluation of swallowing (EES) is not commonly used by gastroenterologists to evaluate swallowing in patients with dysphagia.